Figuring rural development concepts and cases of land use, sustainability and integrative indicators - Hobbes, Marieke 1976- (LUP dissertations, 2010)
This research, with empirical data from the Philippines, Vietnam, India, and Laos, represents a merger of environmental science and rural development economics. It develops a unique measuring rod of wealth and poverty: Freely Disposable Time, which integrates time and cash flow of households to quantify concepts of freedom and development capacity.